The Effect of Self-Protecting Techniques On Walking Skills In Student With Visual Impairment Houses’s - Alby, Muhamad; Meiyani, Neni (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
Self-protection technique is one of the important skills that must be possessed by students with visual impairment, where this technique is one part of the mobility orientation. Mobility orientation skills must be possessed by every students with visual impairment so that they can work independently. However, in reality there are not a few students who have not mastered mobility orientation skills even though in their immediate environment, namely the home environment, such as the case found in SLB Aisyiyah Kawalu, namely on the subject of SLN. This study was conducted to determine how much influence self-protection techniques have on walking skills in the home environment on blind students, namely SLN. This study uses a quantitative approach and experimental methods, with the independent variable being self-protection techniques and the dependent variable being traveling independence. Data collection in this study used one cycle, namely (Baseline 1 – Intervention 1 – Baseline 2) which was analyzed using descriptive statistics. The results of this study show that the percentage from baseline 1 is 35%, intervention is 55%, and in baseline condition 2 it is 65%. So, it can be concluded from the results of this study that there is a change in SLN in walking skills in the home environment, using self-protection techniques SLN begins to walk in the home environment independently.